A Comparative Study of Inflammatory Markers in Diabetics versus Non- Diabetics with Covid-19 and their Impact on Morbidity and Mortality Outcomes - Subramanian, Vathul B; H, Basavanagowdappa; Kulkarni, Praveen (Archives of Clinical and Biomedical Research, 2023)
Background and Aims: COVID-19 pandemic has been one of the most devastating public health emergency of 21st century. Diabetic patients tend to have a poorer prognosis compared to non-diabetics. In this study, we aimed to study the inflammatory markers (Ferritin, Lactate Dehydrogenase, C - reactive protein, Erythrocyte Sedimentation Rate, D-Dimer) in diabetics and non-diabetics with COVID-19 and their impact on morbidity and mortality. Methods: This was a hospital-based combined retrospective and prospective study conducted among 1000 patients who presented with COVID-19 to a Tertiary Care Hospital in South India over a duration of 18 months from December 2020 to May 2022 after obtaining clearance from the institutional ethics committee and written informed consent from the study participants. They were divided into two groups-diabetics and nondiabetics. Their COVID and diabetes related morbidities were compared with the levels of their inflammatory markers like ESR, D-Dimer, Ferritin, LDH, CRP and IL-6. Results: Among, 1000 subjects included in our study, 46% were diabetics. Males suffered the brunt of the disease (66%). Patients with higher HbA1c had more mortality (P value <.001). Diabetics had prolonged hospital stays, more oxygen requirement and a higher chance of requiring Non Invasive Ventilation (NIV) and mechanical ventilation. They also had more complications like acute respiratory distress syndrome (ARDS) ARDS, sepsis, acute kidney injury (AKI) and death. (P value 0.01 in all variables). Inflammatory markers like ESR, CRP, D-dimer, ferritin and LDH were compared between both groups. These markers were elevated irrespective of diabetic status and were elevated in all severe cases and its various complications like ventilator requirement and other COVIDrelated complications and death and these parameters were statistically significant. Conclusions: Diabetics had a more adverse outcome in terms of complications and mortality in comparison to non-diabetics with COVID illness. Inflammatory markers like CRP, ESR, D-Dimer, ferritin and LDH were increased in both as the severity of COVID-19 increased indicating that it was an independent prognostic marker in itself.